ANALYSIS OF COMPETENCE YUNIOR HIGH SCHOOL TEACHER TO WELCOMES CURRICULUM 2013 IMPLEMENTATION. (Case Study of Mapping to Yunior High School Teacher in Competence at Bengkalis Subdistrict,Riau Province) - Suharso, Pudjo; Sukidin, Sukidin; Puryanto, Sidik (Universitas Negeri Semarang, 2014)
Policy the implementation of curriculum 2013 that replaced curriculum 2006 is the government effort to improve education in Indonesia. The changed of education policy through the implementation of curriculum 2013 in all level from primary school to secondary school, itâ€™s cause consequences and implication of learning activity Â growth widely. The consequences and implication of learning activities based on curriculum 2013 is not only relating equipments and strategies of learning but also the readyness a teacher as a top actor of learning education at school.The changed of education policy through the implementation of curriculum 2013 is demand to re-analysis of basic competence from teacher due to based on curriculum 2013 explain thatÂ it is not by sparated but integrated subject must being now. The purpose of the research is mapping competence in readiness a teacher of learning activity based on curriculum 2013 at yunior high school. The research of methode is survey by descriptive analysis. The result is a half of teacher at Bengkalis subdistricat have different competence, so caused of unoptimalisation in learning process. Giving rekomendation by resetting required for yunior high school teacher which curriculum 2013 rules.